Teksty polskie w kontekstach pozapolonistycznych - Tokimasa Sekiguchi (Postscriptum Polonistyczne)
Texts that either come from Poland or are used in thinking about Poland can sometimes be very useful in research and discussions that go far beyond the traditional formula of Polish Studies. The author of this article suggests four disciplines for research: the concept of history, Europe, nation and Judaica. Polish texts are needed in these fields and reading them is often essential. Polonists are generally not fully aware of the importance of Polish texts in such contexts and the number of translations of many important Polish texts is still insignificant. The author of the article postulates a change in Polonists’ perspectives.